Studies on the thermal conditions of soils at the upper tree line in the Páramo of Papallacta (Eastern Cordillera of Ecuador) - Bendix, Jörg; Rafiqpoor, M. Daud (ERDKUNDE, 2001)
Microclimatological measurements of soil temperature and soil heat flux in the Páramo of Papallacta are presented in order to describe the thermal growth conditions, especially of forest patches at the upper tree line in comparison to open sites. It has been proven that -0.5 m soil temperature at selected forest sites is significantly lower than is reported for other tropical high mountains. Forest patches at the upper tree line in the Páramo of Papallacta grow below -0.5 m at soil temperatures temporarily of 1.9 °C or a yearly average of about 4.25 °C. However, differences between colder forest soils and the adjacent warmer bunchgrass sites are slighter (~1-2 °C, -0.5 m) than is presented for other investigations in tropical high mountains. This is mainly due to similar soil properties, especially the constant soil moisture in the root zone and the high humus content, which generally causes a low thermal soil conductivity at all sites. Root zone heat flux (-0.1 m), as suggested by previous studies, is not only the result of a reduced sky view factor due to canopy shading of the forest ground. It has proved to be also significantly dependent on the air-soil temperature difference and the influence of turbulence due to an increased wind speed. However, the root zone temperature (-0.1 m) is colder under forest ground which is mainly due to the better thermal insulation by means of a well-developed organic layer (moss-/peat-like) in comparison to the bunchgrass sites. Additionally, the daily mean of root zone temperature is mostly lower than assumed necessary for root growth in the course of studies conducted in the Swiss Alps. Finally, -0.5 m soil temperature is not constant in the course of the year. During the observation period presented here, this was due to a cold La Niña event, probably as a combined effect of increased moisture at deeper soil levels by extensive daily precipitation, increased nocturnal radiation and higher turbulence by cold trades.